Chemical priming of strawberry plants under deficit irrigation enhances yield efficiency and physiological resilience - Georgiadou, Egli C.; Taliadorou, Anna-Maria; Myrtsi, Eleni D.; Torrado, Sofia O.C.A.; Valanides, Nicolas; Bini, Lorenzo; Manganaris, George A.; Fotopoulos, Vasileios (My University, 2025)
Strawberry is a high-value crop with substantial water requirements, rendering it particularly vulnerable to irrigation limitations, especially in regions like the Mediterranean, which is characterized by low summer rainfall and restricted water sources. This study investigated the effects of different priming agents (PAs) on yield efficiency and physiological and biochemical performance of strawberry (Fragaria x ananassa Duch.) cv. 'Red Sayma 1075' grown under deficit irrigation. The experiment was conducted under a commercial strawberry setup in Cyprus, using a randomized complete block design (RCBD) with five blocks serving as biological replicates. The treatments were hydroprimed, 100 µM melatonin (Mel), 0.1% w/v sodium alginate (NaA), 0.1% w/v NaA/100 µM Mel, 2 mM proline, and 0.1% w/v NaA/2 mM proline. Three treatment applications were performed at different times, one at root level of tray plants prior to transplantation and two foliar applications at 8 d and 15 d after transplantation. Plants received 50% of standard irrigation following priming applications to simulate conditions of deficit irrigation. Results demonstrated that Mel, NaA, and NaA/Proline treatments significantly enhanced cumulative yield of early harvest compared with hydroprimed controls. Mel and NaA/Mel displayed significantly higher endogenous Mel content compared with controls. In addition, an array of analysis was conducted ar leaf level at 2, 15 and 29 d after imposition of deficit irrigation. Elevated proline concentrations were observed during early stress stages (2 days), particularly in NaA and NaA/proline treatments. Proline levels were suppressed after 15 d, indicating an adaptive metabolic response in NaA, NaA/Melatonin, proline as well as on NaA/Proline primed plants. Significant downregulation of enzymatic antioxidants (SOD, CAT and H2O2) was also observed in all treatments in the initial stages of stress application and were maintained at low levels throughout the duration of the experiment until 29 days. Thereafter, most biochemical markers returned to baseline levels, indicating stabilization of physiological responses under sustained deficit irrigation. The findings highlight the potential of specific priming strategies, particularly those involving Mel, NaA, and NaA/proline to mitigate drought stress, sustain yield, and improve physiological resilience in strawberry cultivation under water deficit conditions.
Keywords: Fragaria x ananassa; Abiotic stress; Deficit irrigation; Drought stress; Melatonin; Priming; Proline; Sodium alginate; Stress alleviation